Parent-child communication, parental control and parental stimulation their relationship to student's class participation. - Prosia, Rhea P
This study sought to demonstrate the relationship between the variables Parent-Child Communication, Parental Control and Parental Stimulation to the Class Participation variable. Sixty (60) respondents composed of thirteen (13) males and forty-seven (47) females participated in this study. All of them were enrolled in Philosophy 1 classes under one instructor during the Second Semester of AY 2000-2001. Purposive sampling was employed. This study utilized a survey questionnaire with a 5-point frequency scale that was used to measure the variables under investigation. The instrument was consisted of four (4) scales which include the: Class Participation Scale, parent-Child Communication Scale, Parental Control Scale and Parental Stimulation Scale. Spearman Rank-Order Correlation was used to analyze the results. The findings of this study indicated that Parent-Child Communication and Class Participation were significantly correlated with rs = .299 using an alpha of .05, suggesting a direct relationship between the variables. The relationship between Parent-Child Communication and Class Participation was discussed in terms of the studies and personality factors related to communication and class participation. The variables Parental Control and Parental Stimulation were not demonstrated to be related to Class Participation. The findings on the relationships of the Class Participation and the other variables were viewed in the light of limitations of the study.